Structural changes in the economy through the prism of macroeconomic indicators On the example of the Republic of Kazakhstan - Ospanbayev, Zh.A.; Myrzakhmetova, A.M.; Celetti, D. (BUKETOV BUSINESS REVIEW, 2018)
In the context of the post-industrial development of the world economy, the intensification of internationalization and the globalization of international economic relations led to unprecedented structural changes in the economic system of society. The transition of the development of society to a postindustrial stage requires a radical change in the structure of the national economy. Here, first of all, we should pay attention to increasing the share of the sectors of the processing industry and services in the structure of the national economy, as well as their constant support. There are some macroeconomic indicators that characterize the effectiveness of structural changes in the economy. The article analyzes some of these indicators, including changes in the GDP growth rate, the structure of exports and imports, and the employment structure of the population. The results of any structural changes in the economy should bring changes directly to the structure of GDP, exports and imports, the balance of payments, and also to the employment structure of the economy. Structural changes in the economy, carried out during the years of independence, are analyzed and estimates of these changes are given. In conclusion, the need to carry out structural changes in the economy of Kazakhstan under conditions of a decline in world prices for mineral resources is argued.